2017
DOI: 10.18178/ijesd.2017.8.6.984
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Characteristics of Leonardite for Removal of Cd(II) and Zn(II) from Aqueous Solutions

Abstract: Leonardite was used as an adsorbent for the removal of Cd(II) and Zn(II) from aqueous solutions. The characteristics of leonardite were determined using XRD, XRF, FTIR, and SEM. Adsorption of Cd(II) and Zn(II) on leonardite, in batch system at 30 °C, was investigated to achieve the optimum condition for metals removal. Studies were carried out at different pH, contact time, and initial metal concentration. It was found that adsorption of metals ions was strongly influenced by pH value. The optimum adsorption c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The same applies to Gd and Dy as both fit better to Langmuir than Freundlich, assuming the binding of PK216 resin sites is equal in terms of its affinity for the adsorbate. For Gd, the result is in agreement with the literature, where the adsorption energy of PK216 is equivalent to the surface site for Gd 54,55 . In the final stage, the PK216 resin adsorbent reaches equilibrium as the surface becomes saturated with a monolayer of Pr, Gd, and Dy molecules, respectively 37 …”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The same applies to Gd and Dy as both fit better to Langmuir than Freundlich, assuming the binding of PK216 resin sites is equal in terms of its affinity for the adsorbate. For Gd, the result is in agreement with the literature, where the adsorption energy of PK216 is equivalent to the surface site for Gd 54,55 . In the final stage, the PK216 resin adsorbent reaches equilibrium as the surface becomes saturated with a monolayer of Pr, Gd, and Dy molecules, respectively 37 …”
Section: Resultssupporting
confidence: 89%
“…The REE ions must go through external diffusion phases such as liquid film and intraparticle diffusion before reaching the adsorbent surface sites for ion exchange to occur. In general, the adsorption of Pr, Gd, and Dy on PK216 resin is not entirely controlled by intraparticle diffusion; instead, the film diffusion and intraparticle diffusion both influence the diffusion of Pr, Gd, and Dy, thus contributing to the adsorption resistance rate 54,62,63 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the end of the experiment, in which the use of leonardite (another natural adsorbent) together with zeolite has a positive influence on ammonia removal, agrees with the studies of Öz et al (2016) and Şahin et al (2019). Chammui et al (2014) and Terdputtakun et al (2017) demonstrated that leonardite is more beneficial in removing unwanted compounds in aquatic environments. Furthermore, similar to this study, it was reported by Zengin (2013) and Şahin (2022) that the use of a clinoptilolite-leonardite mixture was effective.…”
Section: Discussionmentioning
confidence: 99%